2020
DOI: 10.1101/2020.11.02.364463
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emergence of a cephalosporin reduced susceptible Neisseria gonorrhoeae clone between 2014-2019 in Amsterdam, the Netherlands, revealed by a genomic population analysis

Abstract: Background Emerging resistance to cephalosporins in Neisseria gonorrhoeae (Ng) is a major public health threat, since these are considered antibiotics of last resort. Continuous surveillance is needed to monitor the circulation of reduced susceptible and resistant strains. Aim For the purpose of epidemiological surveillance, a genomic population analysis was performed on Ng isolates from Amsterdam with a focus on ceftriaxone reduced susceptible isolates. Methods Whole genome sequences were obtained from 318 is… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Machine learning models that predict resistance phenotype from genotype rely on datasets that provide both. Regional gonococcal surveillance programs (such as GISP, Euro GASP, WHO‐GASP, and ASGAP) and smaller epidemiological studies have reported genome sequences and AMR profiles from over 18,000 clinical isolates of N. gonorrhoeae ; 16,17,23,49,52–55,57–70,101,102 many of these have been curated and aggregated in databases, such as Pathogenwatch 66 . But the sampling strategies differ among surveillance programs, as can the quality of the sequencing or phenotypic data.…”
Section: Framework For Machine Learning Models For Antimicrobial Susc...mentioning
confidence: 99%
See 1 more Smart Citation
“…Machine learning models that predict resistance phenotype from genotype rely on datasets that provide both. Regional gonococcal surveillance programs (such as GISP, Euro GASP, WHO‐GASP, and ASGAP) and smaller epidemiological studies have reported genome sequences and AMR profiles from over 18,000 clinical isolates of N. gonorrhoeae ; 16,17,23,49,52–55,57–70,101,102 many of these have been curated and aggregated in databases, such as Pathogenwatch 66 . But the sampling strategies differ among surveillance programs, as can the quality of the sequencing or phenotypic data.…”
Section: Framework For Machine Learning Models For Antimicrobial Susc...mentioning
confidence: 99%
“…Much work has been done to determine the genetic modulators of AMR in N. gonorrhoeae , 34–48 with a focus on the antibiotics for which antimicrobial susceptibility test (AST) phenotypes are available—thus, most data are for antibiotics in recent use (ceftriaxone, cefixime, azithromycin, and ciprofloxacin) as well as others for which surveillance programs often collect data (penicillin and tetracycline) 16,17,23,25,49–72 . Most of the loci that account for a large extent of resistance in circulating populations in areas of high surveillance have been well characterized, 66,73 with several recent additions to the list of genetic modulators being described, 18,74–77 including some of increasing prevalence, such as the mosaic mtr 78,79 (where mosaicism refers to interspecies recombination between N. gonorrhoeae and another Neisseria species).…”
Section: Introductionmentioning
confidence: 99%